2020
DOI: 10.1111/add.15154
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and circumstances of death related to the self‐administration of ketamine

Abstract: Background and aims Ketamine is used for anaesthesia, sedation and the treatment of mood disorders, but is also widely used for non‐medical purposes. This study aimed to: (1) determine the characteristics and circumstances of all recorded cases of self‐administered ketamine‐related death in Australia, 2000–19 and (2) determine the toxicology and major organ pathology of cases. Design Retrospective study of all Australian cases in which self‐administered ketamine was a mechanism contributory to death, retrieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…In other studies, the average/mean number of post-mortem drugs recorded in ketamine-related deaths is not provided. The profile of drugs found at post-mortem overlaps with both those found in San Francisco (San Nicolas and Lemos, 2015) and Australia (Darke et al, 2020). The main substances recorded in the NPSAD post-mortem toxicology were: alcohol (41%), cocaine (41%), heroin/morphine (31%), diazepam (28%), MDMA (20%), cannabis (18%) and methadone (10%).…”
Section: Comparison Of Decedents' Characteristics With Other Npsad Casesmentioning
confidence: 73%
See 4 more Smart Citations
“…In other studies, the average/mean number of post-mortem drugs recorded in ketamine-related deaths is not provided. The profile of drugs found at post-mortem overlaps with both those found in San Francisco (San Nicolas and Lemos, 2015) and Australia (Darke et al, 2020). The main substances recorded in the NPSAD post-mortem toxicology were: alcohol (41%), cocaine (41%), heroin/morphine (31%), diazepam (28%), MDMA (20%), cannabis (18%) and methadone (10%).…”
Section: Comparison Of Decedents' Characteristics With Other Npsad Casesmentioning
confidence: 73%
“…This study found that the most common manner of death (i.e. the determination by a coroner or medical examiner as to how a disease or injury led to death) recorded in England during the period 1999-2019 for recreational ketamine-related deaths was accidental (83%) and accounted for a much higher proportion of deaths than in comparable studies: San Nicolas and Lemos (2015) = 17/25; Darke et al (2020) = 40/68, whereas other studies have recorded higher levels of suicides, for example 32% by Darke et al (2020) compared to our study (< 6%), the case definitions are not identical.…”
Section: Safety Of Ketaminementioning
confidence: 81%
See 3 more Smart Citations